TRANSFORMATIONAL CHANGES OF THE MODERN WORLD ECONOMY IN THE CONDITIONS OF GLOCALIZATION AND CRISIS OF GLOBALISM - Arkhipov, Alexey; Yeletsky, Alexey (Revista Inclusiones, 2020)
The purpose of the article is to analyze the contradictory trends in the development of the modern world economic system. The relevance of the topic is due to the multifaceted and ambiguous nature of regionalization, glocalization and fragmentation tendencies formed as the most important trends in the crisis of globalism. Based on the classical methods of historical and functional analysis, system approach and comparative studies, the authors realized the research potential of modern methodological tools, alternative forecasting methods and comparative modeling, as well as special methods of economic globalistics and global political economy. Heuristic possibilities of the methodological-theoretical concept of glocalization of international economic relations are used.